Marketing Collaboration for Educational Tourism Based on Fruit-Farming Production in the Digital Era - Suranto Suranto; Eny Haryati; Amirul Mustofa (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Educational tourism based on fruit-farming production holds great potential, but its marketing management often runs partially and has not yet been collaborative, so destination competitiveness is not yet optimal in the digital era. This study aims to analyze the forms and patterns of collaboration among stakeholders, identify the role of digital media, and formulate a marketing-collaboration model for educational tourism based on fruit-farming production. The study uses a qualitative approach with a case-study strategy at the Fruit Garden Educational Tourism site, Batu City, Malang, East Java. The research population comprised destination stakeholders, while the sample was determined purposively at twelve informants representing five pentahelix elements: government, business actors, community, academics, and media. Data were collected through in-depth interviews, observation, documentation, and digital content analysis, then analyzed using the Miles and Huberman interactive model — data reduction, data display, and conclusion drawing — complemented by content analysis, with validity maintained through triangulation. The results show that collaboration among the five elements has formed but remains informal and incidental, with the manager as the dominant actor. Digital marketing is not yet planned, and content showing visitors' direct experience achieves the highest engagement compared to promotional content. The study concludes that strengthening marketing requires a structured collaboration model covering joint planning, division of roles, joint content production, digital distribution, and periodic evaluation, with the learning experience highlighted as the destination's main value.